An anti-fingerprint transparent hardened film for automotive touch screens

By applying the anti-fingerprint coating of DMAPMA-b-PFPE-b-POSS ternary block copolymer and epoxidized nano-SiO2 on the automotive touch screen, the problem of fingerprint contamination during use is solved, and efficient anti-fouling, good light transmission and wear resistance are achieved.

CN118791930BActive Publication Date: 2025-03-11HUNAN XINGYUE TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411045197.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-03-11
Estimated Expiration
2044-07-31

AI Technical Summary

Technical Problem

Car touch screens are easily contaminated by fingerprints and skin oils during use, affecting their clarity and glossiness. The prior art is difficult to effectively prevent fingerprint contamination.

Method used

The copolymer was prepared by atom transfer radical polymerization reaction using an anti-fingerprint coating including DMAPMA-b-PFPE-b-POSS ternary block copolymer and epoxidized nanoSiO2, and crosslinked with nanoSiO2 to form a film with low surface energy and good adhesion.

Benefits of technology

It realizes excellent hydrophobic and oleophobic properties and easy decontamination performance of the automotive touch screen surface, significantly prevent fingerprint contamination, and maintains good light transmission and wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118791930B_ABST
    Figure CN118791930B_ABST
Patent Text Reader

Abstract

The invention relates to the field of optical films, in particular to an anti-fingerprint transparent hardened film for an automobile touch screen, comprising a substrate and an anti-fingerprint coating; the anti-fingerprint coating comprises a DMAPMA-b-PFPE-b-POSS ternary block copolymer. The anti-fingerprint transparent hardened film prepared by the invention has excellent hydrophobicity and oleophobicity and easy decontamination performance, and good abrasion resistance and light transmittance, and has a significant anti-fingerprint pollution effect, and can be widely used in the protection of automobile touch screens.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of optical films, in particular to an anti-fingerprint transparent hardened film for automobile touch screens. Background Art

[0002] With the development of new energy vehicles, the size of car touch screens is getting larger and larger. Although voice control is developing rapidly, most car owners are accustomed to controlling the screen with their fingers. Residual fingerprints and skin oils are the main factors affecting the clarity and glossiness of the car touch screen surface. How to prevent the touch screen from being contaminated by fingerprints during use and maintain its light transmittance has become a problem that needs to be solved urgently. Summary of the invention

[0003] Purpose of the invention: In view of the above technical problems, the present invention proposes an anti-fingerprint transparent hardened film for automobile touch screens.

[0004] The technical solutions adopted are as follows:

[0005] An anti-fingerprint transparent hardened film for a car touch screen, comprising a substrate and an anti-fingerprint coating;

[0006] The anti-fingerprint coating comprises a DMAPMA-b-PFPE-b-POSS ternary block copolymer.

[0007] Further, the preparation method of the DMAPMA-b-PFPE-b-POSS ternary block copolymer is as follows:

[0008] PFPE-OH was modified with 2-bromoisobutyryl bromide to obtain PFPE-Br, and then DMAPMA-b-PFPE-b-POSS ternary block copolymer was prepared by atom transfer radical polymerization with PFPE-Br as initiator and MAPOSS and DMAPMA as polymerization monomers.

[0009] Further, the preparation method of the DMAPMA-b-PFPE-b-POSS ternary block copolymer is as follows:

[0010] S1: DMAP, TEA and dichloromethane are mixed to obtain solution A, and solution A is cooled to 0-5°C under nitrogen protection. α-Bromoisobutyryl bromide and PFPE-OH are dissolved in dichloromethane to obtain solution B and solution C, respectively. Solution B and solution C are added dropwise to solution A in sequence, and the reaction is resumed to room temperature for 18-36 hours after the addition is completed. After the reaction is completed, water is added and stirred, and the aqueous phase is separated. The organic phase is dried and concentrated under reduced pressure to obtain PFPE-Br;

[0011] S2: PFPE-Br, MAPOSS, CuBr and 2,2-bipyridine were mixed, and the mixture was repeatedly frozen, vacuumed, introduced with protective gas and thawed for 1-3 times, and then sealed and reacted for 5-10 hours. After the reaction, the mixture was passed through a neutral alumina column, and then precipitated with a large amount of n-hexane. The product was collected and dried to obtain an intermediate;

[0012] S3: The intermediate, DMAPMA, CuBr and 2,2-bipyridine are mixed, and the mixture is repeatedly frozen, vacuumized, introduced with protective gas and thawed for 1-3 times, and then sealed and reacted for 5-10 hours. After the reaction, the mixture is passed through a neutral alumina column, and then precipitated with a large amount of n-hexane. The product is collected and dried to obtain the DMAPMA-b-PFPE-b-POSS ternary block copolymer.

[0013] Further, the reaction temperature in S2 and S3 is 100-120°C.

[0014] Furthermore, the anti-fingerprint coating also includes epoxidized nano-SiO2.

[0015] Furthermore, the substrate is any one of glass, PP film, PVC film, PET film or ARM film.

[0016] Furthermore, the preparation method of the above-mentioned anti-fingerprint transparent hardened film for automobile touch screen is as follows:

[0017] The DMAPMA-b-PFPE-b-POSS ternary block copolymer is dissolved in a solvent, epoxidized nano-SiO2 is added, and sodium hydroxide is added after being fully mixed. The spray liquid is obtained after ultrasonic oscillation dispersion, and the spray liquid is evenly distributed on the surface of the substrate and then solidified.

[0018] Further, the preparation method of epoxidized nano-SiO2 is as follows:

[0019] Disperse nano-SiO2 in ethanol, add epoxy silane coupling agent and water, heat to 40-60°C and react for 12-36 hours, centrifuge, collect the product and dry it.

[0020] Furthermore, the epoxy silane coupling agent is KH-560.

[0021] Furthermore, the mass ratio of the DMAPMA-b-PFPE-b-POSS ternary block copolymer to the epoxidized nano-SiO2 is 1-5:1-5.

[0022] Furthermore, curing includes room temperature curing and heating curing, the room temperature curing time is 10-60 minutes, the heating curing temperature is 100-120° C., and the heating curing time is 1-5 hours.

[0023] Beneficial effects of the present invention:

[0024] The present invention provides an anti-fingerprint transparent hardened film for automobile touch screens. Fluorine atoms have a small atomic radius and the largest electronegativity in the periodic table. The mutual repulsion between fluorine atoms in organic fluorine polymers surrounds the carbon chain to form a stable fluorine atom pile, resulting in PFPE having very low surface properties, chemical inertness, and super strong hydrophobicity and oleophobicity.

[0025] The DMAPMA-b-PFPE-b-POSS ternary block copolymer prepared by the present invention through an atom transfer radical polymerization reaction contains two types of low surface energy elements, fluorine and silicon, thereby further reducing the surface energy of the anti-fingerprint coating, and also introduces an amino group that can be cross-linked with epoxidized nano-SiO2, so that the periphery of the nano-SiO2 is cross-linked and wrapped by the copolymer, and a large number of long carbon chain fluorosilicone structures with low surface energy are successfully grafted, which can overcome the adhesion problem of the nano-SiO2 on the substrate surface, can better form a film on the solid surface, thereby improving the adhesion, and avoiding its agglomeration;

[0026] The anti-fingerprint transparent hardened film prepared by the present invention has excellent hydrophobic and oleophobic properties and easy decontamination performance, as well as good abrasion resistance and light transmittance, and has a significant anti-fingerprint pollution effect, and can be widely used in the protection of automobile touch screens. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a schematic structural diagram of the anti-fingerprint transparent hardened film in Example 1;

[0028] The numbers in the figure represent:

[0029] 1-Glass substrate, 2-Anti-fingerprint coating.

[0030] Figure 2 This is the SEM image of the anti-fingerprint coating prepared in Example 1. DETAILED DESCRIPTION

[0031] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0032] DMAP: N,N-dimethylaminopyridine;

[0033] TEA: triethylamine;

[0034] PFPE-OH: perfluoropolyether alcohol;

[0035] MAPOSS: monomethacrylate POSS;

[0036] CuBr: copper bromide;

[0037] DMAPMA: dimethylaminopropyl methacrylamide.

[0038] Embodiment 1:

[0039] An anti-fingerprint transparent hardened film for a car touch screen comprises a glass substrate 1 and an anti-fingerprint coating 2, and the preparation method thereof is as follows:

[0040] S1: 0.915g DMAP, 0.505g TEA and 20ml dry dichloromethane were mixed to obtain solution A. Solution A was cooled to 0-5°C under nitrogen protection. 2.875g α-bromoisobutyryl bromide and 8g PFPE-OH (Mn=1600) were dissolved in 20ml dichloromethane to obtain solution B and solution C respectively. Solution B and solution C were added dropwise to solution A in sequence. After the addition, the mixture was returned to room temperature for reaction for 24h. After the reaction was completed, 60ml water was added dropwise and stirred for 30min. The aqueous phase was separated. The organic phase was dried over anhydrous sodium sulfate and then concentrated under reduced pressure to obtain PFPE-Br.

[0041] S2: PFPE-Br, MAPOSS, CuBr, and 2,2-bipyridine were mixed in a molar ratio of 1:1:1:2, and the mixture was repeatedly frozen, vacuumed, introduced with protective gas, and thawed for 3 times. The mixture was sealed and heated to 120°C for reaction for 8 hours. After the reaction, the mixture was returned to room temperature and passed through a neutral alumina column. A large amount of n-hexane was then added to the reaction solution for precipitation. The product was collected and dried to obtain an intermediate.

[0042] S3: The intermediate, DMAPMA, CuBr, and 2,2-bipyridine were mixed in a molar ratio of 1:3:1:2, and the mixture was repeatedly frozen, vacuumized, introduced with protective gas, and thawed for 3 times, and then sealed and heated to 120°C for reaction for 8 hours. After the reaction was completed, the mixture was returned to room temperature and passed through a neutral alumina column. A large amount of n-hexane was then added to the reaction solution for precipitation. The product was collected and dried to obtain a DMAPMA-b-PFPE-b-POSS ternary block copolymer.

[0043] S4: Disperse 8g of nano-SiO2 in 200ml of ethanol, add 4g of KH-560 and mix well, then drop 10ml of water, heat to 50℃ and react for 24h, centrifuge, collect the product and dry to obtain epoxidized nano-SiO2;

[0044] S5: Dissolve 5g of DMAPMA-b-PFPE-b-POSS ternary block copolymer in 500ml of fluorine oil solvent MX-056, then add 3g of epoxidized nano-SiO2, mix thoroughly and disperse by ultrasonic oscillation for 30min, then dissolve a trace amount of sodium hydroxide in an appropriate amount of ethanol and drop it in, continue to disperse by ultrasonic oscillation for 30min to obtain a spray liquid, first plasma etch the glass substrate 1 for 30s, then ultrasonically clean it, dry it and fix it on the spray bracket, then use a spray gun to evenly spray the spray liquid on the surface of the glass substrate 1 in a dust-free environment with a spray gun pressure of 0.5MPa and a diameter (Φ) of 0.8mm. After spraying two layers, first cure at room temperature for 30min, and then heat and cure at 100°C for 2h to obtain an anti-fingerprint transparent hardened film, see Figure 1 It can be clearly seen that the surface of the anti-fingerprint coating is irregular, rough and uneven, with protrusions and groove-like concave structures.

[0045] Embodiment 2:

[0046] An anti-fingerprint transparent hardened film for a car touch screen comprises a glass substrate 1 and an anti-fingerprint coating 2, and the preparation method thereof is as follows:

[0047] S1: 0.915g DMAP, 0.505g TEA and 20ml dry dichloromethane were mixed to obtain solution A. Solution A was cooled to 0-5°C under nitrogen protection. 2.875g α-bromoisobutyryl bromide and 8g PFPE-OH (Mn=1600) were dissolved in 20ml dichloromethane to obtain solution B and solution C respectively. Solution B and solution C were added dropwise to solution A in sequence. After the addition, the mixture was returned to room temperature for reaction for 24h. After the reaction was completed, 60ml water was added dropwise and stirred for 30min. The aqueous phase was separated. The organic phase was dried over anhydrous sodium sulfate and then concentrated under reduced pressure to obtain PFPE-Br.

[0048] S2: PFPE-Br, MAPOSS, CuBr, and 2,2-bipyridine were mixed in a molar ratio of 1:1:1:2, and the mixture was repeatedly frozen, vacuumed, introduced with protective gas, and thawed for 3 times. The mixture was sealed and heated to 120°C for reaction for 8 hours. After the reaction, the mixture was returned to room temperature and passed through a neutral alumina column. A large amount of n-hexane was then added to the reaction solution for precipitation. The product was collected and dried to obtain an intermediate.

[0049] S3: The intermediate, DMAPMA, CuBr, and 2,2-bipyridine were mixed in a molar ratio of 1:3:1:2, and the mixture was repeatedly frozen, vacuumized, introduced with protective gas, and thawed for 3 times, and then sealed and heated to 120°C for reaction for 8 hours. After the reaction was completed, the mixture was returned to room temperature and passed through a neutral alumina column. A large amount of n-hexane was then added to the reaction solution for precipitation. The product was collected and dried to obtain a DMAPMA-b-PFPE-b-POSS ternary block copolymer.

[0050] S4: Disperse 8g of nano-SiO2 in 200ml of ethanol, add 4g of KH-560 and mix well, then drop 10ml of water, heat to 50℃ and react for 24h, centrifuge, collect the product and dry to obtain epoxidized nano-SiO2;

[0051] S5: Dissolve 5g of DMAPMA-b-PFPE-b-POSS ternary block copolymer in 500ml of fluorine oil solvent MX-056, add 5g of epoxidized nano-SiO2, mix thoroughly and disperse by ultrasonic oscillation for 30min, dissolve a trace amount of sodium hydroxide in an appropriate amount of ethanol and add it dropwise, continue to disperse by ultrasonic oscillation for 30min to obtain a spray liquid, first plasma etch the glass substrate 1 for 30s, then ultrasonically clean it, dry it and fix it on the spray bracket, then use a spray gun to evenly spray the spray liquid on the surface of the glass substrate 1 in a dust-free environment with a spray gun pressure of 0.5MPa and a caliber (Φ) of 0.8mm. After spraying two layers, first cure at room temperature for 30min, and then heat and cure at 100℃ for 2h.

[0052] Embodiment 3:

[0053] An anti-fingerprint transparent hardened film for a car touch screen comprises a glass substrate 1 and an anti-fingerprint coating 2, and the preparation method thereof is as follows:

[0054] S1: 0.915g DMAP, 0.505g TEA and 20ml dry dichloromethane were mixed to obtain solution A. Solution A was cooled to 0-5°C under nitrogen protection. 2.875g α-bromoisobutyryl bromide and 8g PFPE-OH (Mn=1600) were dissolved in 20ml dichloromethane to obtain solution B and solution C respectively. Solution B and solution C were added dropwise to solution A in sequence. After the addition, the mixture was returned to room temperature for reaction for 24h. After the reaction was completed, 60ml water was added dropwise and stirred for 30min. The aqueous phase was separated. The organic phase was dried over anhydrous sodium sulfate and then concentrated under reduced pressure to obtain PFPE-Br.

[0055] S2: PFPE-Br, MAPOSS, CuBr, and 2,2-bipyridine were mixed in a molar ratio of 1:1:1:2, and the mixture was repeatedly frozen, vacuumed, introduced with protective gas, and thawed for 3 times. The mixture was sealed and heated to 120°C for reaction for 8 hours. After the reaction, the mixture was returned to room temperature and passed through a neutral alumina column. A large amount of n-hexane was then added to the reaction solution for precipitation. The product was collected and dried to obtain an intermediate.

[0056] S3: The intermediate, DMAPMA, CuBr, and 2,2-bipyridine were mixed in a molar ratio of 1:3:1:2, and the mixture was repeatedly frozen, vacuumized, introduced with protective gas, and thawed for 3 times, and then sealed and heated to 120°C for reaction for 8 hours. After the reaction was completed, the mixture was returned to room temperature and passed through a neutral alumina column. A large amount of n-hexane was then added to the reaction solution for precipitation. The product was collected and dried to obtain a DMAPMA-b-PFPE-b-POSS ternary block copolymer.

[0057] S4: Disperse 8g of nano-SiO2 in 200ml of ethanol, add 4g of KH-560 and mix well, then drop 10ml of water, heat to 50℃ and react for 24h, centrifuge, collect the product and dry to obtain epoxidized nano-SiO2;

[0058] S5: Dissolve 5g of DMAPMA-b-PFPE-b-POSS ternary block copolymer in 500ml of fluorine oil solvent MX-056, add 1g of epoxidized nano-SiO2, mix thoroughly and disperse by ultrasonic oscillation for 30min, dissolve a trace amount of sodium hydroxide in an appropriate amount of ethanol and add it dropwise, continue to disperse by ultrasonic oscillation for 30min to obtain a spray liquid, first plasma etch the glass substrate 1 for 30s, then ultrasonically clean it, dry it and fix it on the spray bracket, then use a spray gun to evenly spray the spray liquid on the surface of the glass substrate 1 in a dust-free environment with a spray gun pressure of 0.5MPa and a caliber (Φ) of 0.8mm. After spraying two layers, first cure at room temperature for 30min, and then heat and cure at 100℃ for 2h.

[0059] Comparative Example 1:

[0060] The method is basically the same as Example 1, except that no epoxidized nano-SiO2 is added.

[0061] Comparative Example 2:

[0062] The method is basically the same as Example 1, except that nano-SiO2 is directly added, that is, nano-SiO2 is used instead of epoxidized nano-SiO2.

[0063] Comparative Example 3:

[0064] It is basically the same as Example 1, except that perfluorooctyltriethoxysilane (Dixin Chemical) is used instead of the DMAPMA-b-PFPE-b-POSS ternary block copolymer.

[0065] Comparative Example 4:

[0066] The method is basically the same as Example 1, except that the cleaned glass substrate 1 is treated with a commercially available AF anti-fingerprint agent (Longsheng Sihai) instead of the spraying liquid as a comparison.

[0067] Performance Test:

[0068] The anti-fingerprint transparent hardened films prepared in Examples 1-3 and Comparative Examples 1-4 of the present invention were used as samples for performance testing:

[0069] The hydrophobicity and oleophobicity of the anti-fingerprint coating were tested using a static contact angle meter (JC-2000C1), with pure water / edible oil as the probe liquid and a droplet size of 5 μL. The contact angles of 5 different locations on the same coating were tested and the average value was taken;

[0070] Oil-resistant pen test: Take 2 points in the middle of the anti-fingerprint coating, with a middle length of 7cm. Draw a straight line AB between the two points with an oil-resistant pen, and repeatedly wipe the straight line AB with a dust-free cloth until the pen cannot be wiped clean. Record the number of times as N times, and the number of oil-resistant pen times is (N-1) times.

[0071] Light transmittance test: Test the light transmittance of the sample after film formation, using a Cary 5000 UV-visible spectrophotometer, with a wavelength range of 200-800nm;

[0072] Friction resistance test: To test the friction resistance of the anti-fingerprint coating, the anti-fingerprint coating was rubbed at the same position using a LKY-I1 low-speed reciprocating friction and wear tester with a load of 1kg steel wool. The static contact angles at different positions of the friction area were measured three times and the average value was taken. The number of times when the contact angle with water was still greater than 100° was the effective friction resistance number.

[0073] The test results are shown in Table 1 below:

[0074] Table 1:

[0075]

[0076] It can be seen from Table 1 above that the anti-fingerprint transparent hardened film prepared by the present invention has excellent hydrophobicity and oleophobicity and easy decontamination performance, and has good abrasion resistance and light transmittance, and has a significant anti-fingerprint pollution effect, and can be widely used in the protection of automobile touch screens.

[0077] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An anti-fingerprint transparent hardened film for a car touch screen, characterized in that: Including substrate and anti-fingerprint coating; The anti-fingerprint coating comprises a PFPE-b-POSS-b-DMAPMA ternary block copolymer; The preparation method of the PFPE-b-POSS-b-DMAPMA ternary block copolymer is as follows: S1: DMAP, TEA and dichloromethane are mixed to obtain solution A, and solution A is cooled to 0-5°C under nitrogen protection. α-Bromoisobutyryl bromide and PFPE-OH are dissolved in dichloromethane to obtain solution B and solution C, respectively. Solution B and solution C are added dropwise to solution A in sequence, and the reaction is resumed to room temperature for 18-36 hours after the addition is completed. After the reaction is completed, water is added and stirred, and the aqueous phase is separated. The organic phase is dried and concentrated under reduced pressure to obtain PFPE-Br; S2: PFPE-Br, MAPOSS, CuBr and 2,2-bipyridine were mixed, and the mixture was repeatedly frozen, vacuumed, introduced with protective gas and thawed for 1-3 times, and then sealed and reacted for 5-10 hours. After the reaction, the mixture was passed through a neutral alumina column, and then precipitated with a large amount of n-hexane. The product was collected and dried to obtain an intermediate; S3: The intermediate, DMAPMA, CuBr and 2,2-bipyridine are mixed, and the mixture is repeatedly frozen, vacuumized, introduced with protective gas and thawed for 1-3 times, and then sealed and reacted for 5-10 hours. After the reaction is completed, the mixture is passed through a neutral alumina column, and then precipitated with a large amount of n-hexane. The product is collected and dried to obtain the PFPE-b-POSS-b-DMAPMA ternary block copolymer; The anti-fingerprint coating also includes epoxidized nano-SiO2; The preparation method of epoxidized nano-SiO2 is as follows: Disperse nano-SiO2 in ethanol, add epoxy silane coupling agent and water, heat to 40-60℃ and react for 12-36h, centrifuge, collect the product and dry it; The mass ratio of the PFPE-b-POSS-b-DMAPMA ternary block copolymer to the epoxidized nano-SiO2 is 1-5:1-5.

2. The anti-fingerprint transparent hardened film for automobile touch screen according to claim 1, characterized in that: The reaction temperature in S2 and S3 is 100-120°C.

3. The anti-fingerprint transparent hardened film for automobile touch screen according to claim 1, characterized in that: The substrate is any one of glass, PP film, PVC film, PET film or ARM film.

4. The anti-fingerprint transparent hardened film for automobile touch screen according to claim 1, characterized in that: The preparation method is as follows: The PFPE-b-POSS-b-DMAPMA ternary block copolymer is dissolved in a solvent, and epoxidized nano-SiO2 is added. After being fully mixed, sodium hydroxide is added, and the spray liquid is obtained after ultrasonic oscillation dispersion. The spray liquid is evenly distributed on the surface of the substrate and then solidified.

5. The anti-fingerprint transparent hardened film for automobile touch screen according to claim 4, characterized in that: Curing includes room temperature curing and heating curing. The room temperature curing time is 10-60 minutes, the heating curing temperature is 100-120°C, and the heating curing time is 1-5 hours.

Citation Information

Patent Citations

  • Fluorine-containing triblock acrylate copolymer containing POSS and preparation method thereof

    CN106832157A

  • Fluorine-containing polyether-based block copolymer and process for producing the same

    JP2010144080A